2019
DOI: 10.1111/jpc.14597
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Kejian KJ‐8000 bilirubinometer in an Australian setting

Abstract: Aim To evaluate the accuracy of the Kejian 8000 (KJ‐8000) transcutaneous bilirubinometer in infants of differing ethnicity and gestational age. Methods This was a prospective study of infants in the Newborn Care Unit at Gold Coast University Hospital. Transcutaneous bilirubin (TcB) and serum bilirubin (SBR) results were compared using linear regression and a Bland–Altman plot. Predicted indices were calculated to assess the KJ‐8000 as a screening tool using local jaundice management guidelines. Results A total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…However, despite being a non-invasive method, the considerations of financial costs, lack of standardisation guidelines, inaccurate value in Asian and dark-skinned people, and high false-positive results are not yet adopted in our unit. 19 Therefore, despite the latest modalities, direct Coomb's test remains a cost-effective and readily accessible method of detecting neonates at risk of developing severe hyperbilirubinemia and its complications.…”
Section: Discussionmentioning
confidence: 99%
“…However, despite being a non-invasive method, the considerations of financial costs, lack of standardisation guidelines, inaccurate value in Asian and dark-skinned people, and high false-positive results are not yet adopted in our unit. 19 Therefore, despite the latest modalities, direct Coomb's test remains a cost-effective and readily accessible method of detecting neonates at risk of developing severe hyperbilirubinemia and its complications.…”
Section: Discussionmentioning
confidence: 99%
“…These POCT techniques include implantable, wearable, and handheld devices and sensors. 52 Handheld -Jacques, et al 99 FOC-based -SpectRx BiliCheck 100 Handheld 2300 Bilistick 101 Fingerprick 1400 JM-103 102 Handheld 1500 JM-105 102 Handheld 2900 KJ-8000 Meter 103 Handheld 4800…”
Section: The Need For Point-of-care Bilirubin Estimationmentioning
confidence: 99%
“…33,34,35 The accuracy of TcB in infants receiving PT (due to skin bleaching) and its use on preterm neonates has also been subject of discussion. 36,37 Hulzebos and colleagues concluded that PT enhances the well-known underestimation of TSB by TcB in preterm infants, even when measured on an unexposed area of skin in the diaper area. The underestimation of TSB before PT was significantly lower, 44 ± 36 μmol/L, than the underestimation during and after PT, 61 ± 29 and 63 ± 25 μmol/L, respectively.…”
Section: Transcutaneous Bilirubinometrymentioning
confidence: 99%